Pergeseran Arah Transformasi Bisnis Media Cetak di Era Teknologi Informasi (Studi Kasus pada Harian Solopos) - Suryawati, Indah; Rusadi, Udi; Wahid, Umaimah (Avant Garde, 2023)
The transformation of newspapers into online to multiplatform platforms is a necessity. Information technology and digitalization have significantly brought changes in the ways of media industry works. One of the local newspapers that still survives amidst the onslaught of digital technology is Solopos Daily. Solopos Daily realizes that the era of digital technology is the cause of the decline in the number of readers and advertisers. However, Solopos Daily was able to show interesting survival. Placing Solopos Daily as the case, the problem in this research is formulated as follows: how has the change and direction of Solopos Daily's business transformation in the era of digital technology? The research method being used is a holistic single case study with qualitative research. The result of this research revealed that Solopos Daily realized that the era of digitalization technology was responsible for the decrease in the number of readers and advertisers. To overcome the problems, several innovations were implemented in its media business. One of them was establishing a special market division called Integrated Marketing Solution (IMS) that is in charge of advertising, circulation, and a new business unit. This IMS Division is the marketing force for all the existing market potential of Solopos Daily related to information, data, writing, publishing, publication, event organizer, and institution. Although it has been present and developed as a multiplatform media, Solopos Daily still maintains and develops its print version.